Students Stressors and Coping Mechanism - Aperocho, Lyca Yza V.; Capillo, Faith Carol B.; Zamora, John Mark D.; Morbo, Emy A. (Universitas Pendidikan Indonesia (UPI), 2021)
This study entitled Student Stressors and Coping Mechanism was aimed primarily to determine the different factors that can lead to students' stress and how they cope up with this problem. It used a qualitative-descriptive correlational research design to gather data using an adapted online survey questionnaire online to the thirty-eight (38) third-year bachelor students in physical education in Sultan Kudarat State University, the Philippines. The study used purposive random sampling in analyzing the data. Based on the findings of this study, the level of coping mechanism in terms of physical activities, environmental activities, and social and emotional activities are often applicable coping mechanisms when you are stressed while the BPEd students sometimes encountered difficulties in terms of physical stress, mental stress, emotional stress and economics stress and often encountered academic stress. The result shows that there is a significant relationship between the variables and the null hypothesis is accepted. Based on the findings of this study, the researchers conclude that the level of coping mechanism in terms of physical activities, environmental activities, social and emotional activities are applicable coping mechanisms for stressed students. This study suggests a school counselor and parents to look for these students and create a profile status to observe the students both academically and outside of the school.